Electronic paper display based on polar nanorod quantum dots and preparation method thereof
By adding quantum dots or particles of different colors to the electret material of the electronic paper display and using the change in the flip angle of the polar nanorods, the problems of slow response speed and high power consumption of the electronic paper display are solved, achieving efficient full color show.
Patent Information
- Application Number
- CN202411620593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing electronic paper displays have slow response speed and high power consumption. To achieve colorization, color filter films need to be added to reduce light output.
Using an electronic paper display based on polar nanorod quantum dots, the electret material is electretly processed and quantum dots or black and white particles of different colors are added to both ends, so that the flip angle changes under different electric fields, thereby changing the The degree of reflection to ambient light can realize color display.
It significantly shortens the response time of electronic paper, improves the display effect, and reduces power consumption, achieving efficient full-color display.
Smart Images

Figure CN119247662A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of display devices, and in particular relates to an electronic paper display based on polar nanorod quantum dots and a preparation method thereof. Background Art
[0002] Electronic paper is a paper-like display with memory function, reflective and repeatedly changeable content. It has shown great development prospects in electronic reading, personal electronics, product media and other aspects.
[0003] The display principles of electronic paper include microencapsulated electronic ink, rotating ball display, toner display, microcup electrophoretic display, electrochromic display, electrophoretic deposition display, electrowetting display, cholesterol liquid crystal display, and microelectromechanical system display.
[0004] The electronic paper display technology based on electrophoretic ink materials can maintain a steady state for a long time after the power is removed, and the screen can be displayed normally, which is more common in black and white. However, the existing electrophoretic particles have a slow response speed and high power consumption, resulting in a delay in the electronic paper display. To achieve colorization, a layer of color filter film needs to be added, but it reduces the light output rate. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and to provide an electronic paper display based on polar nanorod quantum dots and a preparation method thereof, which can realize colorization of electronic paper, greatly reduce the response time of electronic paper, and improve the display effect.
[0006] To achieve the above object, the technical solution of the present invention is: an electronic paper display based on polar nanorod quantum dots, wherein polarization is achieved by subjecting the electret material of the polar nanorods in the display layer of the electronic paper display to electret treatment.
[0007] In one embodiment of the present invention, quantum dots of different colors or black and white particles are added to both ends of the electret material, so that it can respond to different applied electric fields, causing changes in the flip angle, thereby causing changes in the degree of reflection of external ambient light.
[0008] In one embodiment of the present invention, it also includes a first substrate and a second substrate, the display layer is located between the first substrate and the second substrate, a first electrode is provided on a side of the first substrate away from the display layer, a color filter film is provided on the first electrode, and a second electrode is provided on a side of the second substrate away from the display layer.
[0009] The present invention also provides a method for preparing the electronic paper display based on polar nanorod quantum dots as described above, comprising:
[0010] Step 1, performing a hydrophobic / hydrophilic treatment on one end surface of the electret material, and performing a hydrophilic / hydrophobic treatment on the other end surface of the electret material;
[0011] Step 2, performing electret treatment on the electret material treated in step 1, so that two ends of the electret material have different electrical properties;
[0012] Step 3, adding black particles or white particles and anionic surfactant into Isopar L to obtain negatively charged black particles or negatively charged white particles;
[0013] Step 4, mixing the quantum dots and cationic surfactant, achieving ion exchange by ultrasound or stirring, filtering after standing, and adsorbing the cations on the surface of the quantum dots by physical adsorption to make the quantum dots positively charged, thereby obtaining positively charged quantum dots;
[0014] Step 5: Place the electret material, negatively charged black particles or negatively charged white particles, and positively charged quantum dots into a dispersion medium to obtain polar nanorods.
[0015] In one embodiment of the present invention, in step 1, the method of performing hydrophobic / hydrophilic treatment on the single-end surface of the electret material is as follows:
[0016] (1) Method for hydrophilizing the single-end surface of the electret material
[0017] (1.1) Chemical modification using chemical substances with hydrophilic functional groups (such as hydroxyl, carboxyl, amino, etc.) to chemically graft the single-end surface of the electret material or copolymerize hydrophilic monomers on the single-end surface of the electret material to improve the hydrophilicity, and then plasma treatment (oxygen, water vapor, etc.) or high-temperature oxidation or chemical oxidation is used to form a hydrophilic oxide film on the single-end surface of the electret material, or a surfactant (silane, sulfonate, etc.) is used to reduce the single-end surface energy of the electret material to make the single-end surface of the electret material hydrophilic;
[0018] (1.2) Coating a hydrophilic material (fluorocarbon polymer, polyvinyl alcohol, etc.) on one end of the electret material by physical methods, and then coating using physical vapor deposition, electrochemical deposition, or solution immersion methods;
[0019] (1.3) changing the single-end surface morphology of the electret material by laser etching to form a microstructure to make the single-end surface of the electret material hydrophilic;
[0020] (1.4) preparing a nanostructure by methods including sputtering, electrodeposition, and anodization to make a single end surface of the electret material hydrophilic;
[0021] (2) Method for performing hydrophobic treatment on the single-end surface of the electret material
[0022] (2.1) Chemical modification using chemical substances with hydrophobic functional groups (such as alkyl, fluorocarbon chain, etc.) to chemically graft the single-end surface of the electret material or copolymerize the hydrophobic monomer in the electret material to improve the hydrophobic property, and then form a hydrophobic fluorocarbon film by fluorinated gas plasma treatment;
[0023] (2.2) Coating a hydrophobic material (such as fluorocarbon polymer, polyvinyl alcohol, etc.) on one end of the electret material by physical methods, and then using a plasma method to chemically react on the surface to enhance the hydrophobic properties;
[0024] (2.3) changing the single-end surface morphology of the electret material by laser etching to form a microstructure so that the single-end surface of the electret material is hydrophobic;
[0025] (2.4) The single-end surface of the electret material is made hydrophobic by preparing a nanostructure through methods including sputtering, electrodeposition, and anodization.
[0026] In one embodiment of the present invention, step 2 is specifically implemented as follows:
[0027] The electret material that has been subjected to hydrophilic or hydrophobic treatment is placed in a polar solution or a non-polar solution. The treated electret material has different single-end densities and different hydrophilicity or hydrophobicity, resulting in vertical orientation of the electret material. At this time, a polar solution is placed at one end of the electret material that has been subjected to hydrophilic or hydrophobic treatment, and the electret material is subjected to electret treatment by methods including corona electret, thermal electret, and photo electret. Then, one end of the electret material that has not been subjected to hydrophilic or hydrophobic treatment is placed in a non-polar solution, and the electret material is subjected to electret treatment by methods including corona electret, thermal electret, and photo electret, so that the two ends of the electret material have different electrical properties.
[0028] In one embodiment of the present invention, step 3 is specifically implemented as follows:
[0029] Black particles or white particles and anionic surfactant are added to Isopar L and stirred at 80°C for 6 hours, centrifuged to remove the supernatant, and washed several times with anhydrous ethanol. The particles are centrifuged at 8000 r / min and vacuum dried for 24 hours to obtain negatively charged black particles or negatively charged white particles.
[0030] In one embodiment of the present invention, the electret material includes carnauba wax, K-1 polycarbonate, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride, polyperfluoroethylene propylene, polypropylene, polyethylene, barium titanate (BaTiO3), lead zirconate titanate, zinc oxide, tantalum oxide, aluminum oxide and titanium oxide or silicon nitride.
[0031] In one embodiment of the present invention, the black particles include carbon black particles; the white particles include TiO2 particles; the quantum dots are made of materials including II-VI compounds, III-V compounds, inorganic compounds, organic compounds, etc., preferably silicon quantum dots, germanium quantum dots, cadmium sulfide quantum dots, cadmium selenide quantum dots, cadmium telluride quantum dots, zinc selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, indium phosphide quantum dots and indium arsenide quantum dot materials; the quantum dots include red, green and blue quantum dots, and the particle sizes are 8-10nm, 6-8nm and 4-6nm, respectively.
[0032] In one embodiment of the present invention, the aspect ratio of the polar nanorods is in the range of 50:1-200:1.
[0033] Compared with the prior art, the present invention has the following beneficial effects: the present invention designs a polar nanorod, which, compared with electrophoretic particles, utilizes the control of the voltage changes of the upper and lower plates to achieve different rotation angles of the polar nanorods and different display effects, and can obtain a faster response speed than the migration of electrophoretic particles and greatly reduce power consumption to achieve a more efficient full-color display. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of polar black and white nanorods according to an embodiment of the present invention;
[0035] Figure 2 This is a schematic diagram of a polar black and white nanorod electronic paper display without voltage applied according to an embodiment of the present invention;
[0036] Figure 3 This is a schematic diagram of applying voltage to the polar black and white nanorod electronic paper display according to an embodiment of the present invention;
[0037] Figure 4 This is a schematic diagram of removing voltage from the polar black and white nanorod electronic paper display according to an embodiment of the present invention;
[0038] Figure 5 This is a schematic diagram of applying voltage again to the polar black and white nanorod electronic paper display according to an embodiment of the present invention;
[0039] Figure 6 This is a schematic diagram of polar colored nanorods according to an embodiment of the present invention;
[0040] Figure 7 This is a schematic diagram of a polar nanorod quantum dot electronic paper display without voltage applied according to an embodiment of the present invention;
[0041] Figure 8 This is a schematic diagram of applying voltage to the polar nanorod quantum dot electronic paper display according to an embodiment of the present invention;
[0042] Fig. 9 This is a schematic diagram of removing voltage from the polar nanorod quantum dot electronic paper display according to an embodiment of the present invention;
[0043] Fig.10 This is a schematic diagram of applying voltage again to the polar nanorod quantum dot electronic paper display according to an embodiment of the present invention;
[0044] 1-black particles, 2-white particles, 3-electret material, 4-glass substrate, 5-color filter film, 6-first electrode, 7-first substrate, 8-display layer, 9-second substrate, 10-second electrode, 11-red quantum dots, 12-green quantum dots, 13-blue quantum dots. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings.
[0046] The present invention provides an electronic paper display based on polar nanorod quantum dots, which realizes polarization by subjecting the electret material of the polar nanorods in the display layer of the electronic paper display to electret treatment. Quantum dots of different colors or black and white particles are added to the two ends of the electret material respectively, so as to respond to different applied electric fields, induce changes in the flip angle, and thus cause changes in the degree of reflection of external ambient light. The electronic paper display also includes a first substrate and a second substrate, the display layer is located between the first substrate and the second substrate, a first electrode is provided on the side of the first substrate facing away from the display layer, a color filter film is provided on the first electrode, and a second electrode is provided on the side of the second substrate facing away from the display layer.
[0047] The present invention also provides a method for preparing the electronic paper display based on polar nanorod quantum dots as described above, comprising:
[0048] Step 1, performing a hydrophobic / hydrophilic treatment on one end surface of the electret material, and performing a hydrophilic / hydrophobic treatment on the other end surface of the electret material;
[0049] Step 2, performing electret treatment on the electret material treated in step 1, so that two ends of the electret material have different electrical properties;
[0050] Step 3, adding black particles or white particles and anionic surfactant into Isopar L to obtain negatively charged black particles or negatively charged white particles;
[0051] Step 4, mixing the quantum dots and cationic surfactant, achieving ion exchange by ultrasound or stirring, filtering after standing, and adsorbing the cations on the surface of the quantum dots by physical adsorption to make the quantum dots positively charged, thereby obtaining positively charged quantum dots;
[0052] Step 5: Place the electret material, negatively charged black particles or negatively charged white particles, and positively charged quantum dots into a dispersion medium to obtain polar nanorods.
[0053] The following is the specific implementation process of the present invention.
[0054] like Figure 1 Polar black and white nanorods are prepared from black particles, white particles and electret materials.
[0055] The embodiment of the present invention provides a method for preparing polar black and white nanorods, comprising the following steps:
[0056] Step 1, performing a hydrophobic / hydrophilic treatment on one end surface of the electret material, and performing a hydrophilic / hydrophobic treatment on the other end surface of the electret material;
[0057] Step 2, performing electret treatment on the electret material treated in step 1, so that two ends of the electret material have different electrical properties;
[0058] Step 3, adding black particles or white particles and anionic surfactant into Isopar L to obtain negatively charged black particles or negatively charged white particles;
[0059] Step 4: Place the electret material, negatively charged black particles, and negatively charged white particles into a dispersion medium to obtain polar black and white nanorods.
[0060] Figure 1 The black particles in the polar black and white nanorods include but are not limited to carbon black particles, carbon black, aniline black, lamp black, rattan black, natural graphite black, Mars black, manganese black, perylene black, etc.
[0061] The carbon black particles in the polar black and white nanorods are modified and hydroxylated on the surface by using oxygen plasma in a vacuum; the hydroxylated carbon black is dispersed in a formaldehyde solution, and after heating, an appropriate amount of sodium hydroxide solution is added to react to obtain hydroxymethylated carbon black; the hydroxymethylated carbon black obtained by the reaction is washed, centrifuged, dried and ground to obtain carbon black particles; methyl methacrylate and methacrylic acid are dispersed in ethanol, nitrogen is introduced, and potassium persulfide is added at a temperature of 60-70°C to react to obtain a polymethyl methacrylate copolymer solution; the dried and ground carbon black particles are dispersed in ethanol, the polymethyl methacrylate copolymer solution is added, stirred, dried, and ground to obtain electrically neutral black particles.
[0062] The above black particles and surfactants are added to Isopar L to obtain charged black particles. The surfactants include but are not limited to alkylbenzene sulfonates, alkyl sulfonate salts, alkyl succinate sulfonates, alcoholamine alkylbenzene sulfonates, cyclopentane salts, alkylphenol sulfonates, polyoxyethylene monolaurate, and the like.
[0063] The white particles in the polar black and white nanorods include but are not limited to white titanium dioxide particles, white lead, white zinc, and the like.
[0064] The white particles in the polar black and white nanorods are grafted with KH560 to form TiO2 nanoparticles. 0.1 g of KH560 is dissolved in 150 ml of toluene and placed in a 500 ml round-bottom flask, using a magnetic stirrer and a nitrogen reflux condenser. When methylbenzene begins to reflux, 0.8 g of hydrophilic TiO2 nanoparticles are added to the KH560 toluene solution. The stirring speed is fixed at 400 rpm. The reaction mixture is kept at 110 ° C for 12 h by nitrogen purging. Wash with methanol and ethanol, centrifuge, and obtain TiO2 particles grafted with KH560.
[0065] The above white particles and surfactants are added to Isopar L to obtain charged white particles. The surfactants include but are not limited to alkylbenzene sulfonates, alkyl sulfonate salts, alkyl succinate sulfonates, alcoholamine alkylbenzene sulfonates, cyclopentane salts, alkylphenol sulfonates, polyoxyethylene monolaurate, and the like.
[0066] The electret materials in the above-mentioned polar black and white nanorods include but are not limited to carnauba wax, K-1 polycarbonate, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride, polyperfluoroethylene propylene, polypropylene, polyethylene, etc. The electret materials are subjected to electret treatment by corona electret, thermal electret, photo electret and other methods to form an electret body.
[0067] The electret prepared above and 0.8g black carbon black particles, 0.8g white TiO2 particles and 1g KH560 and 0.100g T-151, 0.075g CH-5 and 0.075g Span 85 were dissolved in 300ml of Isopar L, put into a 500ml three-necked flask, and a magnetic stirrer and a nitrogen reflux condenser were used. The stirring speed was fixed at 400rpm. By nitrogen purging, the reaction mixture was kept at 400rpm for 7h. The reaction mixture was rotated at 6000rpm for 10 minutes to obtain a display liquid of polar black and white nanorods with grafted black and white particles of a dispersion medium.
[0068] Example 1
[0069] like Figure 2 When the prepared electronic paper display is not powered, the polar black and white nanorods are perpendicular to the substrate, and the nanorods do not flip, but are arranged parallel to each other, with one end of the black particles facing upward to absorb the external ambient light. At this time, the polar black and white nanorod electronic paper display appears pure black. If the white particles in the polar black and white nanorods face upward to reflect the external ambient light, the polar black and white nanorod electronic paper display appears pure white.
[0070] Example 2
[0071] like Figure 3After the polar black and white nanorod electronic paper display is powered on, the polar black and white nanorods flip over, and the flipping angle of the polar black and white nanorods changes depending on the driving voltage. At this time, the polar black and white nanorods reflect the external ambient light, and the flipping angle changes, and the amount of reflected light changes at the same time. The reflected light passes through the color filter film and emits red, green, and blue light with different light output amounts to achieve full-color display.
[0072] Example 3
[0073] like Figure 4 When the electric field of the polar black and white nanorod electronic paper display is removed after power is applied, the polar black and white nanorods stop flipping, and the polar black and white nanorods in a microgrid are arranged in parallel and are in a steady state, and the displayed image does not disappear.
[0074] Example 4
[0075] like Figure 5 After the voltage is applied to the polar black and white nanorod electronic paper display again, the polar black and white nanorods continue to reverse, and the flipping angle of the polar black and white nanorods changes accordingly depending on the driving voltage. At this time, the polar black and white nanorods reflect the external ambient light, the flipping angle changes, and the amount of reflected light changes at the same time. The reflected light passes through the color filter film and emits red, green, and blue light with different light output amounts, realizing full-color display.
[0076] like Figure 6 The polar colored nanorods are prepared from quantum dots, black particles or white particles, and electret materials, and the specific implementation is as follows.
[0077] The embodiment of the present invention provides a method for preparing polar colored nanorod quantum dots, comprising the following steps:
[0078] Step 1: First, the electret material is subjected to an electret treatment by methods such as corona electret, thermal electret, and optical electret, so that the two ends of the electret material have different electrical properties.
[0079] Step 2: Perform hydrophobic / hydrophilic treatment on the surface of the electret material.
[0080] Step 3: Add black particles or white particles and anionic surfactant into Isopar L and stir at 80° C. for 6 h. Centrifuge to remove supernatant, add anhydrous ethanol for multiple washings, centrifuge at 8000 r / min and vacuum dry for 24 h to obtain negatively charged black or white particles.
[0081] Step 4: Mix the quantum dots and cationic surfactant, achieve ion exchange by ultrasound or stirring, let stand and then filter to make the quantum dots positively charged.
[0082] Step 5: Place the electret material, charged black particles or white particles, and charged quantum dots into the dispersion medium, and simply test the flipping of the polar nanorods. When the performance meets the requirements, vacuum dry for 48 hours to obtain the desired polar colored nanorods.
[0083] The above-mentioned quantum dots include but are not limited to II-VI group compounds, and can also be selected from III-V group compounds. They can be inorganic compounds or organic compounds. Silicon quantum dots, germanium quantum dots, cadmium sulfide quantum dots, cadmium selenide quantum dots, cadmium telluride quantum dots, zinc selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, indium phosphide quantum dots and indium arsenide quantum dot materials are preferred.
[0084] Before preparing polar colored nanorods, cationic surfactants including but not limited to one or more of hexadecyltrimethylammonium bromide, tetra-n-butylammonium bromide, benzyltrimethylammonium chloride, fatty amine salts, ethanolamine salts, polyethylene polyammonium salts, hexadecylpyridinium bromide, etc. are added, ion exchange is achieved through ultrasound or stirring, and the mixture is filtered after standing to make the quantum dots positively charged.
[0085] The black particles in the above-mentioned nanorods include, but are not limited to, carbon black particles, carbon black, aniline black, lamp black, rattan black, natural graphite black, Mars black, manganese black, perylene black, and the like.
[0086] The carbon black particles in the nanorods are modified and hydroxylated on the surface by using oxygen plasma in a vacuum; the hydroxylated carbon black is dispersed in a formaldehyde solution, and after heating, an appropriate amount of sodium hydroxide solution is added to react to obtain hydroxymethylated carbon black; the hydroxymethylated carbon black obtained by the reaction is washed, centrifuged, dried and ground to obtain carbon black particles; methyl methacrylate and methacrylic acid are dispersed in ethanol, nitrogen is introduced, and potassium persulfide is added at a temperature of 60-70°C to react to obtain a polymethyl methacrylate copolymer solution; the dried and ground carbon black particles are dispersed in ethanol, the polymethyl methacrylate copolymer solution is added, stirred, dried, and ground to obtain electrically neutral black particles.
[0087] The above black particles and anionic surfactant are added to Isopar L to obtain charged black particles. The surfactant includes but is not limited to one or more of fatty acid salts, sulfates, sulfate esters, phosphate esters, amino acid salts, phenol salts, enolates, ketosulfonamide salts, sodium dodecylphenyl cyclate, etc., and ion exchange is achieved by ultrasound or stirring, and the black particles are filtered after standing to make them negatively charged.
[0088] The white particles in the polar colored nanorods include but are not limited to white titanium dioxide particles, white lead, white zinc, and the like.
[0089] The white particles in the polar colored nanorods are grafted with KH560 to form TiO2 nanoparticles. 0.1 g of KH560 is dissolved in 150 ml of toluene and placed in a 500 ml round-bottom flask, using a magnetic stirrer and a nitrogen reflux condenser. When methylbenzene begins to reflux, 0.8 g of hydrophilic TiO2 nanoparticles are added to the KH560 toluene solution. The stirring speed is fixed at 400 rpm. The reaction mixture is kept at 110 ° C for 12 h by nitrogen purging. Wash with methanol and ethanol, centrifuge, and obtain TiO2 particles grafted with KH560.
[0090] The above white particles and anionic surfactant are added to Isopar L to obtain charged white particles. The surfactant includes but is not limited to one or more of fatty acid salts, sulfates, sulfate esters, phosphate esters, amino acid salts, phenol salts, enolates, ketosulfonamide salts, sodium dodecylphenyl cyclate, etc., and ion exchange is achieved by ultrasound or stirring, and the white particles are filtered after standing to make them negatively charged.
[0091] The electret materials in the above-mentioned nanorods include but are not limited to carnauba wax, K-1 polycarbonate, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride, polyperfluoroethylene propylene, polypropylene, polyethylene, etc. The electret materials are subjected to electret treatment by corona electret, thermal electret, photo electret and other methods to form an electret body.
[0092] The electret prepared above and 0.8g positively charged quantum dot, 0.8g negatively charged black carbon black particles or 0.8g negatively charged white TiO2 particles and 1g KH560 and 0.100g T-151, 0.075g CH-5 and 0.075g Span85 were dissolved in 300ml Isopar L, put into 500ml three-necked flask flask, use magnetic stirrer and nitrogen reflux condenser. Stirring speed is fixed at 400rpm. By nitrogen purge, reaction mixture was kept at 400rpm for 7h hours. Again reaction mixture was rotated with 6000rpm to obtain the display liquid of the polar colored nanorod of the grafted black and white particles with dispersion medium in 10 minutes.
[0093] Example 5
[0094] like Figure 7 When the polar nanorod quantum dot electronic paper display is not powered, the polar colored nanorods are perpendicular to the substrate and do not flip, but are arranged parallel to each other, with one end of the black particles facing upward to absorb the external ambient light. At this time, the polar nanorod quantum dot electronic paper display appears pure black. If the white particles in the polar black and white nanorods face upward to reflect the external ambient light, the polar black and white nanorod electronic paper display appears pure white.
[0095] Example 6
[0096] like Figure 8 After the polar nanorod quantum dot electronic paper display is powered on, the polar colored nanorods flip over, and the flipping angle of the polar colored nanorods changes depending on the driving voltage. At this time, the polar colored nanorods reflect the external ambient light, the flipping angle changes, and the amount of reflected light changes at the same time, emitting red, green, and blue lights of different light output amounts, and achieving full-color display by controlling different voltages.
[0097] Example 7
[0098] like Fig. 9 When the electric field of the polar color nanorod electronic paper display is removed after power is applied, the polar color nanorods stop flipping, and the polar color nanorods in a microgrid are arranged in parallel and are in a steady state, and the displayed image does not disappear.
[0099] Example 8
[0100] like Fig.10 After the voltage is applied to the polar nanorod quantum dot electronic paper display again, the polar colored nanorods continue to reverse, and the flipping angle of the polar colored nanorods changes accordingly depending on the driving voltage. At this time, the polar colored nanorods reflect the external ambient light, the flipping angle changes, and the amount of reflected light changes at the same time, emitting red, green, and blue lights with different light output amounts, and achieving full-color display by controlling different voltages.
[0101] The above are preferred embodiments of the present invention. Any changes made according to the technical solution of the present invention, as long as the resulting functions do not exceed the scope of the technical solution of the present invention, belong to the protection scope of the present invention.
Claims
1. An electronic paper display based on polar nanorod quantum dots, characterized in that: Polarization is achieved by subjecting the electret material of the polar nanorods in the display layer of the electronic paper display to an electret treatment.
2. The electronic paper display based on polar nanorod quantum dots according to claim 1, characterized in that: Quantum dots of different colors or black and white particles are added at both ends of the electret material so that it can respond to different applied electric fields, causing changes in the flipping angle, thereby causing changes in the degree of reflection of external ambient light.
3. An electronic paper display based on polar nanorod quantum dots according to claim 1 or 2, characterized in that: It also includes a first substrate and a second substrate, the display layer is located between the first substrate and the second substrate, a first electrode is provided on the side of the first substrate away from the display layer, a color filter film is provided on the first electrode, and a second electrode is provided on the side of the second substrate away from the display layer.
4. A method for preparing an electronic paper display based on polar nanorod quantum dots according to any one of claims 1 to 3, characterized in that: include: Step 1, performing a hydrophobic / hydrophilic treatment on one end surface of the electret material, and performing a hydrophilic / hydrophobic treatment on the other end surface of the electret material; Step 2, performing electret treatment on the electret material treated in step 1, so that two ends of the electret material have different electrical properties; Step 3, adding black particles or white particles and anionic surfactant into Isopar L to obtain negatively charged black particles or negatively charged white particles; Step 4, mixing the quantum dots and cationic surfactant, achieving ion exchange by ultrasound or stirring, filtering after standing, and adsorbing the cations on the surface of the quantum dots by physical adsorption to make the quantum dots positively charged, thereby obtaining positively charged quantum dots; Step 5: Place the electret material, negatively charged black particles or negatively charged white particles, and positively charged quantum dots into a dispersion medium to obtain polar nanorods.
5. The method for preparing an electronic paper display based on polar nanorod quantum dots according to claim 4, characterized in that: In step 1, the method of performing hydrophobic / hydrophilic treatment on the single-end surface of the electret material is as follows: (1) Method for hydrophilizing the single-end surface of the electret material (1.1) Chemical modification using a chemical substance with a hydrophilic functional group to chemically graft a single-end surface of the electret material or copolymerize a hydrophilic monomer on a single-end surface of the electret material to improve the hydrophilicity, and then plasma treatment or high-temperature oxidation or chemical oxidation is used to form an oxide film with hydrophilic properties on the single-end surface of the electret material, or a surfactant is used to reduce the single-end surface energy of the electret material to make the single-end surface of the electret material hydrophilic; (1.2) coating a hydrophilic material on one end of the electret material by a physical method, and then coating by physical vapor deposition, electrochemical deposition, or solution immersion; (1.3) changing the single-end surface morphology of the electret material by laser etching to form a microstructure to make the single-end surface of the electret material hydrophilic; (1.4) preparing a nanostructure by methods including sputtering, electrodeposition, and anodization to make a single end surface of the electret material hydrophilic; (2) Method for performing hydrophobic treatment on the single-end surface of the electret material (2.1) chemical modification using a chemical substance with a hydrophobic functional group to chemically graft a single end surface of the electret material or copolymerize a hydrophobic monomer in the electret material to improve the hydrophobic property, and then forming a hydrophobic fluorocarbon film by fluorinated gas plasma treatment; (2.2) coating a hydrophobic material on one end of the electret material by physical methods, and then using a plasma method to chemically react the surface to enhance the hydrophobic properties; (2.3) changing the single-end surface morphology of the electret material by laser etching to form a microstructure so that the single-end surface of the electret material is hydrophobic; (2.4) The single-end surface of the electret material is made hydrophobic by preparing a nanostructure through methods including sputtering, electrodeposition, and anodization.
6. The method for preparing an electronic paper display based on polar nanorod quantum dots according to claim 4, characterized in that: The specific implementation of step 2 is as follows: The electret material that has been subjected to hydrophilic or hydrophobic treatment is placed in a polar solution or a non-polar solution. The treated electret material has different single-end densities and different hydrophilicity or hydrophobicity, resulting in vertical orientation of the electret material. At this time, a polar solution is placed at one end of the electret material that has been subjected to hydrophilic or hydrophobic treatment, and the electret material is subjected to electret treatment by methods including corona electret, thermal electret, and photo electret. Then, one end of the electret material that has not been subjected to hydrophilic or hydrophobic treatment is placed in a non-polar solution, and the electret material is subjected to electret treatment by methods including corona electret, thermal electret, and photo electret, so that the two ends of the electret material have different electrical properties.
7. The method for preparing an electronic paper display based on polar nanorod quantum dots according to claim 4, characterized in that: The specific implementation of step 3 is as follows: Black particles or white particles and anionic surfactant are added to Isopar L and stirred at 80°C for 6 hours, centrifuged to remove the supernatant, and washed several times with anhydrous ethanol. The particles are centrifuged at 8000 r / min and vacuum dried for 24 hours to obtain negatively charged black particles or negatively charged white particles.
8. The method for preparing an electronic paper display based on polar nanorod quantum dots according to claim 4, characterized in that: The electret material includes carnauba wax, K-1 polycarbonate, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride, polyperfluoroethylene propylene, polypropylene, polyethylene, barium titanate (BaTiO3), lead zirconate titanate, zinc oxide, tantalum oxide, aluminum oxide and titanium oxide oxide or silicon nitride.
9. The method for preparing an electronic paper display based on polar nanorod quantum dots according to claim 4, characterized in that: The black particles include carbon black particles; the white particles include TiO2 particles; the quantum dots are made of materials including II-VI compounds, III-V compounds, inorganic compounds, and organic compounds; the quantum dots include red, green, and blue quantum dots, and the particle sizes are 8-10nm, 6-8nm, and 4-6nm, respectively.
10. The method for preparing an electronic paper display based on polar nanorod quantum dots according to claim 4, characterized in that: The aspect ratio of the polar nanorods is in the range of 50:1-200:1.
Citation Information
Patent Citations
Quantum dot / polyurethane nano crystal complex and preparation method thereof as well as colorful conversion film
CN103709731A
Active substrate and display device
CN104090361A
LC-based optical display system
CN106796369A
Quick-response quantum dot electronic paper display and preparation method thereof
CN111221196A
Electrophoretic displays using nanoparticles
US20020145792A1
